Evaluation of Clinical Profile and Etiopathology for Hoarseness of Voice- A Study of 146 Cases - Rao Vengala, Ramachandra; Kapilavaya, Nagamanohar; rao Suraneni, Visweswara (International Journal of Medical Research and Review, 2015)
Background: Hoarseness of voice is the most common symptom related to laryngeal pathology and may be caused due to mild upper respiratory tract infections to life threatening laryngeal malignancies. Aim: The aim of this study is to evaluate various causes, predisposing factors and clinical profile of patients presenting with hoarseness of voice. Design: It is an observational study. Materials and methods: 146 patients attended to Otolaryngology department with h/o hoarseness of voice during the period of JAN 2013 to DEC 2014 were included. Primary information was obtained by detailed history, Clinical ENT examination and video laryngoscopy and imaging studies. Various laryngeal causes were identified and evaluated. Statistical analysis was done using standard methods. Results: Out of total 18,200 patients examined, 146(0.8%) found to have hoarseness of voice. Male to female ratio was 1.28:1.Common age group involved was 31-40 years in 54(36.98) cases. Common etio pathologies included Acute laryngitis in 45(30.82%) cases, chronic laryngitis in 29(19.86%), vocal nodules in 18 (12.32%), vocal cord palsy in 11(7.53%) and vocal cord malignancy in 19(13.01%) patients. Common Predisposing factors were smoking in 43(29.45%) cases and vocal abuse in 37(25.34%) cases. Conclusion: Most of the etiopathological factors found in this study were treatable and significant numbers of patients were having neoplastic disease. So, early diagnosis with the help of videolaryngoscopy and imaging can reduce the morbidity and mortality.